Respuesta :

Answer:

See Below.

Step-by-step explanation:

I'm going to take the equation to be

y = x3 + 2x2 + 3x + 6

That is, the first term is a typo

make 2 groups. Put brackets around both groups.

group 1: x^3 + 2x^2   Take out the common factor of x^2

group 1: x^2(x + 2)

group 2: 3x + 6       Take out the common factor of x^2

group 2: 3(x + 2)

Now put the two groups together

Cubic = group 1 + group 2

Cubic = x^2 (x + 2) + 3(x + 2)

Now take out the common factor of x + 2

Cubic = (x + 2) (x^2 + 3)